The Computer Based Tests: a digital substitution for the Iraqi postgraduate students - Abbas, Ammar Awni (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The wide spread of Computer Based Test in the Iraqi universities raised an important concern for some scholars thinking about integrating computers as an academic assessment tool before making big change in the examination systems, that concern is: how the computerized test score is effected in comparison to old paper and pencil . This paper researches whether test scores of Iraqi students varies in the computer, Pencil based tests, sixty-four postgraduate graduates from Iraqi universities. Thirty five female and twenty nine male, all graduated from colleges of science in specializations other than computer science and applying for postgraduate studies in the Iraqi public universities. Therefore are obliged to get the Iraqi computer skills certification for the postgraduate studies, those students chose the computer center in the University of Baghdad to get that certificate. The findings of the study confirmed that postgraduate candidates test scores were not distinctive in the PC based test and in the paper based test, which drove us to presume that PC based testing can be considered as a promising elective method for the logical postgraduate candidates in Iraq.